Wear response of impregnated diamond bits - Mostofi, Masood; Richard, T.; Franca, L.; Yalamanchi, S. (Elsevier BV, 2018)
© 2018 Elsevier B.V. The drilling response of impregnated diamond (ID) bits is controlled by processes involved in the rock fragmentation, and also the wear processes that continuously change the bearing surface of diamonds and bonding matrix. Due to the co-existence of these two processes both affecting the overall drilling response but differently based on drilling conditions (operating parameters, bit, rock and drilling fluid), the response of ID bits has been found inconsistent and difficult to interpret. In this paper, wear mechanisms of impregnated diamond bits are studied using a series of precise state of the art cutting and drilling experiments conducted with impregnated diamond bits and segments. The wear responses are decomposed into three phases of polishing, fracturing and sharpening, and the response in each phase is analyzed using interface laws in terms of depth of cut, and the extents of frictional contacts. The variation of the response at various operating parameters (weight on bit and depth of cut) are obtained and conceptual models characterizing the drilling response under both weight-on-bit and depth of cut conditions are presented.